The Differences of Chemistry Learning Outcome Through the Implementation of Think-Talk-Write (TTW) Type of Cooperative Learning Model and Scramble Type in Teaching Atomic Structure - Alfinda D. Nande; Minarni R. Jura; Ratman Ratman (Universitas Tadulako, 2021)
This research aimed to determine the differences of chemistry learning outcome through the implementation of scramble type of cooperative learning model and think-talk-write (TTW) type in teaching atomic structure at class XI of SMA Negeri 1 Pamona Selatan. This research was a quasi-experiment with a non-randomized pretest-posttest control group design. It was conducted by arranging two groups in which class XI Natural Science 1 as experimental group 1 (n = 21) and class XI Natural Science 2 as experimental group 2 (n = 20). The data of the research were analyzed using a one-party t-test statistic with the prerequisite test, normality test, and homogeneity. The result of data analysis obtained, X̅1 value of chemistry learning on the students of experimental class 1 was 79.86 (SD = 7.15), whereas in the experimental class 2 students X̅2 value was 73.95 (SD = 8. 26). The result of hypothesis testing was obtained t > t1 - α was 2.55> 1.68 with significant level (α = 0.05) and degrees of freedom = 42. This showed that Ho was rejected and Ha was accepted so that it can be concluded that there were differences in chemistry learning outcome through the implementation of scramble type of cooperative learning model and think-talk-write (TTW) type in teaching atomic structure at class XI of SMA Negeri 1 Pamona Selatan.